The Degree of Engaging Ninth Grade Students in The Islamic Education Textbook - Kataa, Sawsan AbdelRaouf; Abu Sneineh, Odeh AbdelJawad (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to reveal the degree of involving the ninth graders in Jordan in the Islamic Education Book through the texts, activities, and questions provided in the book. To achieve the objectives of the study, the researcher used the Romey method to calculate the coefficients of ninth graders’ involvement. The results showed that the coefficients of the texts for the ninth graders is not acceptable according to the coefficient of Romey, and its values in the two parts of the book are (0.32) and (0.12), respectively. The results also showed a low involvement of students in the activities of the Islamic Education Book, which amounted to (0.34) and (0.23) in the first and second parts of the book respectively. As for their involvement through questions, it was acceptable in the second part of the book, reaching (0.40); however, the coefficient of students’ involvement in the first part of the book was (0.35), which showed it does not provide effective questions for students to conduct inquiry and self-learning processes and discover information for themselves. The study recommended devoting more attention to the involvement of the students in the educational content of the Islamic Education Book and activating the content of the book to improve its communication with students. It also recommended conducting more analytical studies on students’ involvement in the Islamic Education books and decreasing the use of abstract facts and definitions which dictate information on students. It also suggested reducing the use of conclusions and explicit generalizations which represent the author’s inferred opinion.